Sepsis as an important risk factor for gastrointestinal bleeding in acute coronary syndrome patients: Two case reports. Issue 36 (September 2018) - Yang, Qi-Yu; Ouyang, Jing; Yang, Jia-Dan
Abstract: Rationale: Sepsis is a common stressor that may decrease microcirculation in the gastrointestinal tract in patients and increase the gastrointestinal bleeding risk of stress-related mucosal disease. However, the CRUSADE (Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines) bleeding risk score, recommended by authoritative guidelines for acute coronary syndrome (ACS), does not include sepsis as a bleeding risk factor. Patient concerns: The 2 cases were about ACS with hemorrhagic complications. The first patient was an 88-year-old man with hypertension, gallstones, hepatic cysts, and chest pain; the second one was a 79-year-old man with chest pain and hypertension. These 2 ACS patients had no bleeding on admission; however, both patients suffered apparent gastrointestinal bleeding immediately after the development of sepsis or severe sepsis. Diagnoses: Both patients were diagnosed as ACS with sepsis. Interventions: The first ACS patient had no use of proton pump inhibitors (PPIs) for prophylaxis prior to the diagnosis of sepsis. The second one was administered PPIs at standard oral doses. Outcomes: The first patient suffered from gastrointestinal bleeding immediately after the onset of sepsis. And oral PPIs failed to prevent upper gastrointestinal bleeding for the second patient, when severe sepsis developed. However, the second patient's gastrointestinal hemorrhage gradually stopped immediately after high doses of PPIs were administered intravenously, rather than orally. When sepsis developed again, the second patient also had no recurrent gastrointestinal bleeding under the protection of PPIs at standard oral doses. Lessons: Our report suggests that sepsis may be an important bleeding risk factor for ACS patients, and the reasonable use of PPIs to prevent gastrointestinal bleeding could be vital for ACS patients complicated with sepsis.